An overview of e-payment adoption among muslim micro-entrepreneurs in Malaysia - Mohamad, Siti Aisyah; Kassim, Salina (Global Economic Excellence, 2017)
The electronic payment (e-payment) system has become an increasingly important payment system world-wide. Apart from improving the convenience, e-payment system also increases the efficiency in the delivery of financial services to “un-bankable” community, especially the micro-entrepreneurs. In Malaysia, the number of e-payments made per capita has increased substantially from 14.3 transactions in 2003 to 82 transactions in 2015. Realizing the increasing importance of e-payments, financial institutions including microfinance institutions should play their roles in encouraging high adoption of e-payment among the micro-entrepreneurs. Up to 2011, there are 645,136 small and medium enterprises being established in Malaysia and of this, 77 per cent is categorized as micro-enterprises. By targeting the micro- entrepreneurs, financial inclusion can be enhanced through adoption epayment system. This study aims to analyze the e-payment services offered to the microenterprises by reviewing the adoption of Muslim micro-entrepreneurs and providing suggestions for the e-payment adoption. In achieving these objectives, the study reviews the existing literature on the adoption of e-payments and highlights the related issues relating to its adoption especially by the micro-entrepreneurs. The findings of this study are expected to enrich the knowledge on the adoption of digital financial services, particularly the e-payment and will be useful for the service providers to continuously improve their services.